2012
DOI: 10.1016/j.chemphys.2011.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Structural distributions from single-molecule measurements as a tool for molecular mechanics

Abstract: A mechanical view provides an attractive alternative for predicting the behavior of complex systems since it circumvents the resource-intensive requirements of atomistic models; however, it remains extremely challenging to characterize the mechanical responses of a system at the molecular level. Here, the structural distribution is proposed to be an effective means to extracting the molecular mechanical properties. End-to-end distance distributions for a series of short poly-L-proline peptides with the sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 74 publications
0
14
0
Order By: Relevance
“…To address this, we first replaced the native linker that connects these domains (residues 264–272, SAEKEEQEK) with a nine-residue poly-proline segment (9Pro). As outlined above, poly-proline was used because the side chain of this residue merges into its backbone, so the dihedral angles are relatively stable, with Φ=−78° and Ψ=+146°, resulting in a rigid helix with a periodicity of three 33 34 35 ( Fig. 1a ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To address this, we first replaced the native linker that connects these domains (residues 264–272, SAEKEEQEK) with a nine-residue poly-proline segment (9Pro). As outlined above, poly-proline was used because the side chain of this residue merges into its backbone, so the dihedral angles are relatively stable, with Φ=−78° and Ψ=+146°, resulting in a rigid helix with a periodicity of three 33 34 35 ( Fig. 1a ).…”
Section: Resultsmentioning
confidence: 99%
“…Proline is a unique amino acid; its side-chain merges with its backbone, thus restricting the backbone dihedral angles to a limited range 33 34 . These properties underlie the finding that short poly-proline segments form rigid helices with a periodicity of three (note: the structures of longer poly-proline motifs, beyond 12–15 residues, can be complex because of the increasing probability of introducing cis proline conformations 35 ). Because of this rigidity, short poly-proline rods have been used as spectroscopic rulers, or rigid spacers, for decades 34 35 36 37 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies demonstrated that the end-to-end distances of the poly-L-proline peptides are shorter than those of perfectly rigid type II proline helices, probably because of the small number of cis isomers interspersed in aqueous solutions of poly-L-proline peptides [3639]. Nevertheless, the end-to-end distance was reported to increase with an increase in the number of proline residues, up to at least 24 amino acids [38]. Therefore, the repeat number of the Pro residue in the linker is expected to control the distance between PCNA2 and PdX, and to subsequently affect the spatial arrangement of PdX relative to P450cam in PUPPET-P n .…”
Section: Discussionmentioning
confidence: 99%
“…We also estimated that the mean end-to-end distance of helical linker Pro 20 was approximately 50 Å according to a previous study [38]. PdX and P450cam are located on the same side of the PCNA ring because they are fused to the C-termini of PCNA2 and PCNA3, respectively.…”
Section: Discussionmentioning
confidence: 99%